Efeito da alantoína sobre a úlcera gástrica: estudo do mecanismo gastroprotetor - Silva, Dayane Moreira da (2019)
Gastric ulcer affects people worldwide and the recurrence have fueled for new therapeutic strategies. Despite the well-known use of allantoin in cosmetic products, it effect has never been studied in gastric ulcer. In this way, the presente work aimed explore the pharmacological pathways associated with the allantoin efficacy against commonly harmful agents that cause injuries to the stomach. The gastroprotective activity of this compound was evaluate in diferent experimental models induced by ethanol, ethanol acidity and pylorus ligature. All the experimental protocols were approved by CEUA/UFG, protocol n. 064/15. Female albino Swiss mice (30-35g) were used in the experiments. They were maintained at 23  2C and 12 h light/dark cycle, with free access to food and water. Animals were fasted 16 h before the experimental sessions with free access to glucose water (5%). The stomach of mice were used to quantification of reduced gluthatione (GSH), gastric vascular permeability, pro-inflammatory cytokines (TNF- e IL-1), gastric mucus, PGE2 levels and the myeloperoxidase (MPO) activity. The gastric lesions were examined macroscopically and histopatological analysis in light microscopy and eletronic microscopic transmission were carried out. The results showed that allantoin at dose of 60 mg/kg (p.o.) decreased the formation of gastric lesion in all the experimental models and the intraduodenal treatment revealed the antisecretory action. The treatment with allantoin preserved the GSH levels and decreased the gastric vascular permeability, MPO activity and pro-inflammatory cytokines levels. The treatment with allantoin preserved the gastric adhered mucus as well as the PGE2 levels. Microscopic and ultrastructural analysis revealed that allantoin maintained tissue integrity and prevented morphological changes in cells caused by ethanol. Altogether, the results of present work brings evidences that allantoin possesses gastroprotective activity through anti-oxidative, antisecretory, and cytoprotective mechanisms.